2016
DOI: 10.1039/c5nr06595j
|View full text |Cite
|
Sign up to set email alerts
|

Chitin and carbon nanotube composites as biocompatible scaffolds for neuron growth

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34][35][36][37][38] In addition, interests have also been generated to study the effects of nanoparticles on neurons and there are several reports that suggest that nanoparticles promote neuronal differentiation, and neuroprotection studied in both in vitro and in vivo conditions. 3,[39][40][41][42][43] To get better therapeutic results, various types of nanoparticles have been studied in neurons, and among those, carbon-based nanoparticles are mostly reported, 4,[44][45][46][47][48] followed by gold and silver nanoparticles (AgNPs). [49][50][51] Despite having many beneficial properties, nanoparticle also raises few health hazard and toxicity issues.…”
Section: Introduction Of Nanoparticlesmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37][38] In addition, interests have also been generated to study the effects of nanoparticles on neurons and there are several reports that suggest that nanoparticles promote neuronal differentiation, and neuroprotection studied in both in vitro and in vivo conditions. 3,[39][40][41][42][43] To get better therapeutic results, various types of nanoparticles have been studied in neurons, and among those, carbon-based nanoparticles are mostly reported, 4,[44][45][46][47][48] followed by gold and silver nanoparticles (AgNPs). [49][50][51] Despite having many beneficial properties, nanoparticle also raises few health hazard and toxicity issues.…”
Section: Introduction Of Nanoparticlesmentioning
confidence: 99%
“…Some reports revealed ES could promote correct reinnervation and help axons cross the nerve repair site or nerve guidance channels, but it did not increase the speed of axonal elongation [44][45][46][47][48][49][50]. Besides, ES was believed to activate neuronal differentiation [35,51,52], and robust neuron regeneration was observed in vivo experiments on conductive materials with ES [53,54]. Recent studies found enhanced neurite outgrowth following ES [41,55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the chitin can be modified to augment its electrical conductivity. Recently, the addition of carbon nanotubes to a chitin scaffold was shown to increase in electrical conductivity, synaptic function, and viability of engineered neurons [61]. …”
Section: Natural Polymersmentioning
confidence: 99%